Management of the Obstetric Fistula in Burundi: the experience from a multidisciplinary approach over 5 years - Mareschal, Gaetan; Morren, Geert; vanden Boogaard, Wilma; Dominguez, Eva (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To reduce maternal morbidity and improve the quality of life of women with obstetric fistula (OF) in Burundi. Methods: A permanent multidisciplinary OF Center was opened in 2010 offering comprehensive care to women with OF including nursing, surgery/anesthesia, medical care, physiotherapy, psycho-social support and education on family planning and nutrition. Outreach activities were conducted to detect patients together with awareness campaigns. Referral system was strengthened through health workers orientation. Results: There were 1559 first admissions and 479 re-admissions. Closure rates and continence rates at discharge after OF surgery were 77% and 61% respectively at the first intervention, and 58% and 41% at repeated intervention. All women with closed OF but incontinences 3 days after bladder catheter removal received physiotherapy. 260 vulnerable women received personal psycho-social support. 4760 health’s workers were given OF orientation and referral from health facilities increased from 14 to 40% in 5 years. Conclusions: OF Center’s care was efficient, affordable and to a certain degree sustainable. Lessons learned on the management of clinical data, the simultaneous offer of different interventions and the provision of diverse trainings show that providing multidisciplinary OF care is very complex and demands specific expertise and continuous monitoring.